2020
DOI: 10.1371/journal.pcbi.1008480
|View full text |Cite
|
Sign up to set email alerts
|

A functional theory of bistable perception based on dynamical circular inference

Abstract: When we face ambiguous images, the brain cannot commit to a single percept; instead, it switches between mutually exclusive interpretations every few seconds, a phenomenon known as bistable perception. While neuromechanistic models, e.g., adapting neural populations with lateral inhibition, may account for the dynamics of bistability, a larger question remains unresolved: how this phenomenon informs us on generic perceptual processes in less artificial contexts. Here, we propose that bistable perception is due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 88 publications
(147 reference statements)
4
5
0
Order By: Relevance
“…This positive priming exhibits rather different characteristics (e.g., shape-, size- and motion-specificity, inducement period, persistence period) than the negative priming/adaptation of rivaling representations ( de Jong et al, 2012 ; Pastukhov et al, 2013a ; Pastukhov and Braun, 2013b ; Pastukhov et al, 2014a ; Pastukhov et al, 2014b ; Pastukhov, 2016 ). To our mind, this evidence suggest that sensory memory is mediated by additional levels of representation and not by self-stabilization of rivaling representations, as has been suggested ( Noest et al, 2007 ; Leptourgos, 2020 ). To incorporate sensory memory, the present model would have to be extended to include three hierarchical levels (evidence, decision, and memory), as previously proposed by Gigante et al, 2009 .…”
Section: Discussionsupporting
confidence: 64%
“…This positive priming exhibits rather different characteristics (e.g., shape-, size- and motion-specificity, inducement period, persistence period) than the negative priming/adaptation of rivaling representations ( de Jong et al, 2012 ; Pastukhov et al, 2013a ; Pastukhov and Braun, 2013b ; Pastukhov et al, 2014a ; Pastukhov et al, 2014b ; Pastukhov, 2016 ). To our mind, this evidence suggest that sensory memory is mediated by additional levels of representation and not by self-stabilization of rivaling representations, as has been suggested ( Noest et al, 2007 ; Leptourgos, 2020 ). To incorporate sensory memory, the present model would have to be extended to include three hierarchical levels (evidence, decision, and memory), as previously proposed by Gigante et al, 2009 .…”
Section: Discussionsupporting
confidence: 64%
“…Previous work has linked ascending loops with psychotic symptoms, including auditory hallucinations, persecutory delusions, and jumping-to-conclusions bias, and low vulnerability to illusions in schizophrenia (Jardri et al, 2017;Notredame et al, 2014). Additionally, we have suggested that mild (descending) loops might play an important role in normal brain function (Jardri et al, 2017) and underlie common perceptual phenomena such as bistable perception (Leptourgos et al, 2020c(Leptourgos et al, , 2020a. Here, we extended those ideas by showing that different loops can generate very different aberrant perceptual phenomena.…”
Section: Discussionsupporting
confidence: 65%
“…Conversely, an "ascending loop" (also called "climbing loop") is generated when the sensory evidence corrupts the prior, leading to the amplification of the likelihood and an overinterpretation of sensory data. Such circularity could be an important feature of perceptual inference in humans (Leptourgos et al, 2020c(Leptourgos et al, , 2020a, while in extreme cases, it could generate psychotic symptoms, including hallucinations and delusions (Bouttier et al, 2021;Jardri et al, 2017). This idea is in line with related theories that postulate that schizophrenia may result from an impairment in the brain's predictive mechanisms (Adams et al, 2013;Corlett et al, 2019;Fletcher and Frith, 2009;Leptourgos and Corlett, 2020;Powers et al, 2017;Sterzer et al, 2018).…”
Section: The Circular Inference Frameworksupporting
confidence: 56%
“…The bidirectional and selective disruption of the working memory representations that are communicated between cortical areas following the inactivation of local target area activity provides direct evidence for the mechanistic role of functional cortical feedback loops in the maintenance of internally generated cognitive representations. Such mechanisms have previously been proposed to account for the influence of latent variables, such as priors or contextual information, on sensory processing in hierarchical models of visual perception 23 , 54 , 55 , 64 . Our results therefore suggest that common neural substrates—specifically, high-dimensional population codes—may implement internal models in the brain, independent of their sensory causes and motor consequences.…”
Section: Discussionmentioning
confidence: 99%